2014
DOI: 10.1111/1750-3841.12370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemp (Cannabis sativa L.) Seed Oil Press‐Cake and Decaffeinated Green Tea Leaves (Camellia sinensis) on Functional Characteristics of Gluten‐Free Crackers

Abstract: Hemp seed oil press-cake as a by-product of cold-pressed oil processing and brown rice flour were used to design a functional gluten-free snack-type product-savory crackers. All crackers were high in minerals, fibers, and omega-3 fatty acids with a desirable omega-6/omega-3 fatty acids ratio. Green tea leaves were added to improve antioxidant activity, which greatly contributed to their functional properties. This qualified the crackers as a healthy snack with a minimal content saturated fatty acids and an abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 45 publications
5
59
0
3
Order By: Relevance
“…Conversely, flavonols presented an extensive decrease (62-82%) after treatment Morales et al (2015) carotenoids, among others) (Capriles et al, 2016). Other studies have reflected the potential for the use of hemp seeds (Rado caj et al, 2014), flaxseeds (Girma et al, 2013) and chia seeds (Costantini et al, 2014) in different gluten-free matrices for the enhancement of the antioxidant capacity of the final products without affecting notably the technological parameters assessed. Flours used as ingredients could also be obtained from apple (Morales et al, 2015), apple pomace (Mir et al, 2015) or jambolan .…”
Section: Additives Gluten-free Matrices (%)mentioning
confidence: 99%
“…Conversely, flavonols presented an extensive decrease (62-82%) after treatment Morales et al (2015) carotenoids, among others) (Capriles et al, 2016). Other studies have reflected the potential for the use of hemp seeds (Rado caj et al, 2014), flaxseeds (Girma et al, 2013) and chia seeds (Costantini et al, 2014) in different gluten-free matrices for the enhancement of the antioxidant capacity of the final products without affecting notably the technological parameters assessed. Flours used as ingredients could also be obtained from apple (Morales et al, 2015), apple pomace (Mir et al, 2015) or jambolan .…”
Section: Additives Gluten-free Matrices (%)mentioning
confidence: 99%
“…However, some authors (Callaway and others ; Svennerstedt and Svensson ) have reported hemp seeds as useful materials for animal feed production due to its high levels of edible oil. In Canada, various commercial hemp‐seed‐derived products are available such as snacks, defatted meal, protein shakes, hemp milk (vanilla or chocolate flavored), energy bars, and oils (House and others ; Radocaj and others )). The composition of hemp seed protein (HSP) as an excellent natural source of highly digestible amino acids when compared to other protein sources such as borage meal, canola meal, and heated canola meal has been documented (Wang and others ).…”
Section: Introductionmentioning
confidence: 99%
“…10 Byproducts of hemp processing have the potential to be used as ingredients in the formulation of specialty products for human consumption. 11,12 However, the content of different nutritional and antinutritional compounds in hemp meal has not yet been reported. Therefore, the main objective of this study was to characterize the types and content of nutritional and antinutritional compounds in hemp meal and to determine to what extent the separation of hemp meal by sieving affected their distribution between the resulting fractions.…”
Section: ■ Introductionmentioning
confidence: 99%